The Concept of Terrorism and Implementation of the Principles of Criminalization in the Law on the Eradication of Criminal Acts of Terrorism - Bardi, Ahmad; Nurhayani (CV. Inara, 2021)
Terrorism is one of the crimes that greatly disturbs the security of the life of the nation and state. Terrorism is not only a problem for the Indonesian people, but has become an international problem. The eradication of criminal acts of terrorism in Indonesia is carried out based on Law Number 5 of 2018 in conjunction with Law Number 15 of 2003. The problem that becomes the object of research is the concept of terrorism and the implementation of criminalization principles in the law on eradicating criminal acts of terrorism. The type of research used is normative legal research with a statute approach, conceptual approach, historical approach, and comparative approach. The results of research in the law on eradicating criminal acts of terrorism have limited the definition of terrorism by including ideological, political and security disturbance motives, in contrast to other countries which on average do not include motives in the definition of terrorism. The principles of criminalization in the preparation of the law on the eradication of criminal acts of terrorism have not been fully fulfilled, namely about avoiding the formulation of vague and general articles.